Impact of the COVID-19 Pandemic on Municipal Finance - World Bank (Washington, DC: World Bank, 2022)
City local governments have been facing multiple challenges due to the COVID-19 pandemic to secure adequate financial resources for response and recovery. This report assesses the impact of the pandemic on local governments’ financial situations through cross-country analysis and comparison. Three indicative types of local government adjustments are discussed and scenario analysis is used to highlight the risks and uncertainties associated with the pandemic’s impact and subsequent economic recovery.